Comprehensive management of Mayer-Rokitansky-Küster-Hauser syndrome management: A case report - Mishra, Sanskar; Sapkale, Bhagyesh; Singh, Shreya; Jha, Asha; Chaudhari, Kamlesh (Narra Sains Indonesia, 2024)
Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome, also known as Müllerian aplasia, is a congenital condition characterized by uterine and upper vaginal aplasia. It affects females with a normal female karyotype and typical secondary sex characteristics. The aim of this case report was to highlight the multidisciplinary management approach for MRKH syndrome, focusing on tailored interventions to address physical and psychological challenges and improve reproductive prospects. A 26-year-old married female presented to Acharya Vinoba Bhave Rural Hospital (AVBRH), Sawangi, Wardha, India in January 2023 with primary amenorrhea. Physical examination revealed a blind vagina and a hypoplastic uterus, indicative of MRKH syndrome. Further evaluation, including pelvic magnetic resonance imaging (MRI), confirmed Müllerian duct abnormalities and bilateral ovarian anomalies. The absence of a functional vagina significantly impacted the patient's quality of life, leading to difficulties with sexual intercourse and emotional distress related to infertility. A collaborative approach involving a gynecologist and a psychiatrist at AVBRH was initiated to address these challenges. The patient underwent vaginoplasty to create a neovagina, enhancing the sexual function and intimate relationship with the spouse. However, due to the hypoplastic uterus, achieving motherhood through traditional means was not possible. Therefore, assisted reproductive techniques, in particular surrogacy, were explored. Normal, functional ovaries were harvested from the patient for use in surrogacy procedures. This comprehensive management strategy exemplifies the challenges associated with MRKH syndrome and underscores the importance of tailored interventions and long-term follow-up. The case highlights the significance of collaborative care in improving the quality of life and reproductive prospects for individuals with MRKH syndrome.